?CATALYTIC CONVERSION OF CYCLOHEXANE TO ADIPIC ACID USING OXYGEN UNDER MILD CONDITIONS: Short Communication (Biological Sciences - PJSIR, 1999)
The present paper is. based on studies carried out forreplacement of HN03 using oxo trinuclear complexes of Ru,Rh, Nb, Mo and Fe with dicarboxylic acids and the study ofadipic acid preparation reaction mechanism.